2019
DOI: 10.1002/jper.18-0644
|View full text |Cite
|
Sign up to set email alerts
|

Histatin‐1 counteracts the cytotoxic and antimigratory effects of zoledronic acid in endothelial and osteoblast‐like cells

Abstract: Background: Zoledronic acid, the most frequent agent associated with bisphosphonate-related osteonecrosis of the jaw (BRONJ), has been reported as cytotoxic for bone and vascular cells. Hence, identification of novel approaches aiming to counteract its cytotoxic effects will be desirable to develop preventive therapies for BRONJ. The salivary peptide Histatin-1 was recently shown to promote oral wound healing, by acting in epithelial and endothelial cells; however, its effects on cells exposed to zoledronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 39 publications
(56 reference statements)
2
20
0
Order By: Relevance
“…However, due to the large variety of biomaterials, there is still an apparent great need for broadly applicable approaches to promote cell spreading on biomaterials. Previously, we and others showed that Hst1 promoted adhesion, spreading, and migration of various epithelial cells from different origins, such as mucosa , gingiva , cornea , and skin , endothelial cells , and osteogenic cells . All together, these findings underline a non‐cell type‐specific character of Hst1 rendering a promising application potential for tissue engineering purposes.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…However, due to the large variety of biomaterials, there is still an apparent great need for broadly applicable approaches to promote cell spreading on biomaterials. Previously, we and others showed that Hst1 promoted adhesion, spreading, and migration of various epithelial cells from different origins, such as mucosa , gingiva , cornea , and skin , endothelial cells , and osteogenic cells . All together, these findings underline a non‐cell type‐specific character of Hst1 rendering a promising application potential for tissue engineering purposes.…”
Section: Resultssupporting
confidence: 52%
“…A promising candidate cell‐targeting agent to promote cell–substrate interactions is histatin‐1 (Hst1), a member of a large histidine‐rich salivary peptide family. Our previous findings show that Hst1 can significantly promote the attachment, spreading, and migration of various cell types including epithelial, endothelial, and osteogenic cells . Our recent data confirm that Hst1 can promote the spreading of osteogenic cells on both bio‐inert glass and titanium surface , which suggests a promising application potential of Hst1 in the cell‐based bone tissue engineering.…”
supporting
confidence: 65%
“…From the above described results it may be deducted that the absence of amino sequences 1-11 in Hst2 and 23-38 in Hst5 (compared to Hst1) dramatically compromised their uptake rates. Consequently, we assessed the uptake dynamics and subcellular targets of truncated variants, F-Hst1 1-11 , F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] to explore their role in the cellular uptake of Hst1, Hst2 and Hst5. CLSM images revealed that the uptake of the truncated variants F-Hst1 1-11 , F-Hst1 12-22 and F-Hst1 [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] was much lower than that of the whole molecule F-Hst1 ( Figure 7A-D).…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
“…At 60 min post-incubation Hst1 showed a mean fluorescence of 2.00 ± 0.15 × 10 6 AFU, which was significantly higher than that of F-Hst1 12-22 (0.25 ± 0.03 × 10 6 AFU), F-Hst1 1-11 (0.07 ± 0.00 × 10 6 AFU) and F-Hst1 23-38 (0.07 ± 0.00 × 10 6 AFU) ( Figure 7F). F-Hst1 [12][13][14][15][16][17][18][19][20][21][22] mainly co-localized with the lysosomal marker (P coloc value of 0.55 ± 0.12, not with markers for the mitochondria or the ER or Golgi (Figure 8). Figure 7.…”
Section: Uptake Dynamics and Subcellular Target Of Truncated F-hsts mentioning
confidence: 99%
See 1 more Smart Citation